Serial image media for writing narrative text skills - Lestari, Elisabeth Rosalinda Putri (CV. Mitra Palupi, 2021)
Background: Â Using the media, the students are able to do proper sorting and treatment in learning activities.Purpose: This study aims to determine the effect of the application of serial image media on writing narrative text skills.Design and methods: This research uses a quantitative approach. The type used is a Quasi Experimental Design research, this design has a control group, but does not fully function to control the external variables that affect the implementation of the experiment. The research design used is the Non Equivalent Control Group Design.Results: The result showed that the experimental group obtained an average score of 82.86 and the control group obtained an average score of 71.18. the use of serial image media has a positive effect on writing narrative text skills of stu-dents in grade V Cipinang Besar Utara 7 Elementary school.